Study guide II, chapters 13-27, to accompany Accounting principles [by] Jerry J. Weygandt, Donald E. Kieso, Wlater G. Kell - Kieso, Douglas W. (Wiley, 1996)
The most complete guide available to help professionals sharpen their accounting and business skills. This unique reference features a logically structured framework that details accounting practices step-by-step, as well as all the newest innovations in the field.